Fluxograma eletrônico sobre arboviroses com orientações para idosos e profissionais da saúde - Noronha, Lúcia de Fátima Mororó (2019)
Introduction: arboviruses have been a topic debated in different health spaces, in search of awareness, risk prevention and better care, especially in the elderly population, as they are more vulnerable to arboviruses. Emerging diseases with cyclical presentation, with atypical and severe manifestations in the elderly population, Dengue, Chikungunya and Zika promote organic changes, with Chikungunya being responsible for more deaths in the elderly, due to cardiac changes, with the possibility of diagnosis in the acute phase. Objectives: to evidence scientific production on cardiac alterations in the elderly with Chikungunya; to know what health professionals and the elderly think about arboviruses; propose an electronic flowchart on arboviruses with guidance for the elderly and health professionals. Method: this is a methodological research, starting with an integrative review addressing the theme of cardiac changes in the elderly by Chikungunya; then, an interview with 50 health professionals and 50 elderly people about the knowledge of arboviruses and the care for the elderly population, the interviews were semi-structured, recorded, with a sociodemographic questionnaire, at the Infectious and Parasitic Diseases services of the Lauro Wanderley University Hospital and the Complex Hospital Clementino Fraga in João Pessoa-PB. The texts were processed in the IRaMuTeQ software, later the speeches were analyzed, which helped in the elaboration of the electronic flowchart on arboviruses with guidelines for the elderly and health professionals. Results and discussion: it was observed in the literature review that the cardiac alterations caused by Chikungunya in the elderly cause cardiac lesions that can be diagnosed in the acute phase of the infection or last for months due to the absence of cardiac exams, reducing physical capacity due to the degree of severe insufficiency or even progressing for death, justifying the need for further clarification about the exams, symptoms, and factors that can worsen with arbovirus. About what health professionals and the elderly think about arboviruses, it was identified that most professionals know little about the policy, about the rights in the care of the elderly in health services and about the manifestations of severity in the elderly. However, the elderly spoke more about the symptoms of arboviruses and less about their rights to care and the severity of these diseases; but, analyzing the texts described and comparing them with the literature, it is noted that the elderly do not enjoy their rights in care. The services are not planned to receive them and on the symptoms and severity of infections; they confuse the clinical differences between arboviruses and the most frequently cited serious manifestations were rheumatic diseases, linked to Chikungunya and hemorrhages linked to Dengue. As for the prevention of arboviruses, health professionals and the elderly know the basic preventive measures. Final considerations: it is expected that this flowchart will bring benefits to the care of the elderly through the dissemination of the conducts and practices addressed, which may provide well-being and quality of life in the healthy aging process, promoting the strengthening of public policies for the elderly in the Unified Health System.